Pengembangan Penuntun Praktikum Berorientasi Chemoentrepreneurship pada Kelas XI Semester Genap SMA/MA - Agus Rabialdi , Latisma Dj (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2019)
Guidance Practical oriented Chemoentrepreneurship can be used as teaching materials to help students cultivate practical and entrepreneurial interests. The aims of this research is to create Guidance Practical oriented Chemoentrepreneurship were then tested the validity and practicality that can be used as teaching materials in learning Chemistry grade XI SMA / MA. Type of this research is the Research and Development (R & D). Development model used is 4-D models that consists of four steps : define, design, develop, and disseminate. Guidance Practical oriented Chemoentrepreneurship was validated by 6 validators and practicality was tested by 2 teachers of chemistry and 30 students of class XI IPA SMAN 9 Padang academic year 2016/2017. The results of the analysis average moment kappa was 0.86 with highest category. The test results based on questionnaire responses teacher practicality average moment kappa was 0.92 and a test based on the practicality of student questionnaire responses average moment kappa was 0.82 which are in very highest category. Based on these results of the research, it can be conclude Guidance Practical oriented Chemoentrepreneurship was valid and practical in the learning chemistry process on the second semester grade XI SMA / MA.